A Mini-Review of the Anticancer Properties of Cryptotanshinone: A Quinoid Diterpene Extracted From the Root of Salvia miotiorrhiza Bunge - Naziri, Mahdyieh; Ghafari, Arezoo; Mehrabi, Hoda; Ramezannezhad, Elham; Nazari, Farzaneh; Ansari, Arina; Nikzad, Farhad; Deravi, Niloofar (Frontiers in Drug Discovery, 2022)
Cancer is among the most life-threatening diseases worldwide. Along with conventional therapies like chemotherapy, surgery, and radiotherapy, alternative treatment approaches such as traditional Chinese medicine have attracted considerable public and scientific interest that could be beneficial for patients diagnosed with cancer. Salvia miltiorrhiza Bunge is greatly beloved for its roots and is extensively applied for various disease therapies, including cancers in traditional Chinese medicine. In this review, we intend to summarize the anti-cancer properties of Cryptotanshinone (CPT), an extract of Danshen (the root of Salvia miltiorrhiza Bunge), on different types of cancer.